From Bid Time Return to Somewhere in Time: Matheson as adapter, adaptation as transformation, and the perks of infidelity - Ben Kooyman (Universitat Autònoma de Barcelona, 2014)
This essay closely examines the adaptation of Richard Matheson’s science-fiction romance novel Bid Time Return (1975) into the film Somewhere in Time (1980), scripted by Matheson, directed by Jeannot Szwarc, and starring Christopher Reeve and Jane Seymour in the lead roles. Whilst Bid Time Return was awarded the World Fantasy Award, many of Matheson’s loyal readers, as the author has noted, found the novel «soft», and neither it nor its film adaptation were commercially successful. However, both novel and film have developed loyal followings, with Somewhere in Time even spawning its own fan club, the International Network of Somewhere in Time Enthusiasts. In addition, the film is noteworthy as a critical transformation of its own source text.